Plasma lipoprotein(a) levels: a comparison between diabetic and non-diabetic patients with acute ischemic stroke - Holanda Maurus Marques de Almeida; Filizola Rosália Gouveia; Costa Maria José de Carvalho; Andrade Rodrigo Vasconcelos C.L. de; Silva José Alberto Gonçalves da (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The aim of this study was to evaluate lipoprotein(a) (Lp(a)), total cholesterol, high density lipoprotein cholesterol (HDL), low density lipoprotein cholesterol (LDL), very low density lipoprotein cholesterol (VLDL ), triglycerides , apolipoprotein A (apo A) and B100 (apo B100), uric acid, glycaemic and insulin plasmatic concentrations in patients affected by acute stroke. In this group of patients, we have compared the variables between type 2 diabetic patients and non-diabetic patients. METHOD: We evaluate a total of 34 non-diabetic patients (22 males and 12 females; mean age 66.71 ± 10.83 years) and a group of 26 type 2 diabetic patients (15 males and 11 females; mean age 66.35 ± 9.92 years) in a cross-sectional study. RESULTS: Mean Lp(a) concentration did not significantly differ between type 2 diabetic patients and non-diabetic subjects (29.49 ± 23.09 vs 44.81 ± 44.34 mg/dl). The distribution of Lp(a)levels was highly skewed towards the higher levels in both groups, being over 30 mg/dl in 50%. Lp(a) concentration was positively correlated with abdominal adiposity, using waist-hip ratio(WHR)(p< 0.05). No association was found between Lp(a) and others risk factors like sex, age, other lipidic parameters and the presence of stroke. CONCLUSIONS: Our results showed that there were no significant differences between diabetic and non-diabetic patients' serum Lp(a) levels, which indicates that elevated Lp(a) levels were associated with ischemic stroke, irrespective of the presence of type 2 diabetes mellitus (type 2 DM).